Molecular Mechanism: Inhibition of Fusarium oxysporum T-2 Toxin Synthesis by Surfactin in Dried Fish: Induction of Yap1 Nucleation by ROS Accumulation - Qi Deng; Xueting Ren; Qin Hu; Yuehua Pu; Lukman Iddrisu; Anand Kumar; Meifang Hua; Jianmeng Liao; Zhijia Fang; Ravi Gooneratne (Molecules)
(1) T-2 toxin synthesized by Fusarium oxysporum (F. oxysporum) can cause deterioration of dried fish and endanger human health. (2) The molecular mechanism by which antibacterial lipopeptides surfactin inhibited F. oxysporum growth and toxin production was elucidated by investigating the intracellular ROS production pathway and the subcellular distribution and transcriptional activity of the transcription factor Yap1 and its regulation of Tri5 gene in F. oxysporum. (3) Surfactin caused hyphal damage and nucleic acid and protein leakage; thus, the growth of F. oxysporum was disrupted. Surfactin’s excessive accumulation of intracellular ROS triggered the translocation of transcription factor Yap1 into the nucleus, resulting in toxin cluster gene Tri5 expression inhibition, thereby blocking T-2 toxin synthesis. (4) This is a novel mechanism by which surfactin inhibits the growth and T-2 toxin synthesis of F. oxysporum from multiple aspects, including cell structural integrity and the ROS-Yap1 signaling pathway. (5) This study provides a theoretical basis for the application of surfactin in the antifungal control of aquatic dry products.